Mitochondrial DNA common deletion is not associated with thyroid, breast and colorectal tumors in Turkish patients - (:unkn) unknown (SOC BRASIL GENETICA, 2009)
Recently, efforts have been focused on mitochondrial DNA changes and their relation to human cancers. Among them, a 4977 bp deletion of mitochondrial DNA, named common deletion, has been investigated in several types of tumors, with inconsistent results. In this study, we investigated the presence of the common deletion in tissues from 25 breast, 25 colorectal and 50 thyroid tumors and in the adjacent healthy tissues from Turkish patients. Samples from healthy volunteers were also evaluated for comparison. Two PCR-based methods were used for the detection of the common deletion. First, two pairs of primers were used to amplify wild-type and deleted mtDNA. Then, a highly sensitive nested-PCR was performed, to determine low amounts of deleted genomes. By the first method, wild-type mtDNAs were observed in all samples, but a deletion was observed in only six thyroid samples, by using the nested-PCR method. In conclusion, the mitochondrial common deletion was very rare in our study group and did not appear to be not related with cancer.
Keywords: mitochondrial DNA; common deletion; cancer; SOMATIC MUTATIONS; CANCER; DISEASES; GENOME